2018
DOI: 10.1007/s00464-018-6092-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the management of acute cholecystitis in the elderly: population-based cohort study

Abstract: BackgroundAcute cholecystitis is a life-threatening emergency in elderly patients. This population-based cohort study aimed to evaluate the commonly used management strategies for elderly patients with acute cholecystitis as well as resulting mortality and re-admission rates.MethodsData from all consecutive elderly patients (≥ 80 years) admitted with acute cholecystitis in England from 1997 to 2012 were captured from the Hospital Episode Statistics database. Influence of management strategies upon mortality wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 37 publications
1
43
0
2
Order By: Relevance
“…In older patients and patients with underlying diseases, LC after PTGBD, with preoperative assessment may reduce the risk of surgery. A recent meta-analysis also supports this result 30…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In older patients and patients with underlying diseases, LC after PTGBD, with preoperative assessment may reduce the risk of surgery. A recent meta-analysis also supports this result 30…”
Section: Discussionsupporting
confidence: 58%
“…There are limitations to such research, because surgeons choose the healthiest cohort of elderly patients with AC for LC 29. A recent cohort study reported better outcome for elderly patients with LC compared with patients who did not undergo surgery,30 but a possibility of selection bias still exists. In this study, instead of comparing the results according to whether or not surgery is performed on older patients, comparisons were made according to age.…”
Section: Discussionmentioning
confidence: 99%
“…The increased mortality con rms the frailty of elderly people and re ects the results of studies taking the emergency abdominal surgery in the elderly under the scope. These are showing a higher mortality of 8-16% in this group even being treated [18][19][20]. Just to re ect the COVID Situation during our examined period, the total number of COVID positive deaths in Austria was 384 and 27 in whole State Salzburg, Austria [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…While the work-up algorithm for AC in the general population is relatively clear, 6 for the geriatric population it remains controversial and in the large published series to date, the vast majority of octogenarians with AC receive conservative treatment. 19 Urgent surgery for acute cholecystitis in octogenarians has been associated in the literature with increased rates of primary open (47%) and laparoscopicconverted surgeries (with conversion rates ranging from 7 to 36%). 4,13,15 In the present study, the conversion rate in AC was 19% and only 15% of surgeries for AC were performed open.…”
Section: Discussionmentioning
confidence: 99%